A view on bio-linguistic approach towards language learning - Suba, T.; Kumarasamy, M. (International Journal of Psychosocial Rehabilitation, 2020)
THIS paper deals with the bio-linguistic approach towards learning a language and its procurement. The bio-linguistic approach is being compared with the usage based methodology. It is very much certain that the bio-linguistic approach is incomparable with that of any other in light of the fact that it gives increasingly precise and progressively broad views towards the various aspects of human dialects, just as a superior record of the ways youngsters gain human dialects. Recognizing these records, we move around how kid and grown-up language contrast in sentence creation and in sentence understanding. It would be clear that the contrasts oppose clarification utilizing the psychological systems that are summoned by the usage based methodology. Interestingly, the bio-linguistic approach clarifies the subjective parametric contrasts among youngster and grown-up language. Clarifying how youngster and grown-up language contrast and showing that kids see solidarity notwithstanding evident decent variety are due to the signs of the bio-linguistic approach to deal with language obtaining.